Intelligent Query: Open Another Door to 3D Object Retrieval - GAO, Yue (Institutional Knowledge at Singapore Management University, 2010)
The increasing number of available 3D objects makes their efficient retrieval technology highly desired. Extensive research has been dedicated to view-based 3D object retrieval because of its advantage of 2D views for 3D object content representation. In this paradigm, typically the retrieval is accomplished based a set of different views of the query object, and focuses on the 3D object representation, matching and indexing. In this work, we present another aspect towards 3D object retrieval: intelligent query. Intelligent query includes query selection, query description and combination, and assistive query. We will show how this scheme is ideally suit for the 3D object retrieval problem. We conduct experiments on the National Taiwan University 3D Model database and results demonstrated that our approach can improve retrieval performance. Finally, we give insight into the future of the intelligent query for 3D object retrieval.